Congenital disorder of glycosylation type Ia in a Chinese family: Function analysis of a novel PMM2 complex heterozygosis mutation - Dan Zhong; Xiujuan Huang; Taoshan Feng; Jieqing Zeng; Shanshan Gu; Fan Ning; Yue Yang; Jinyuan Zhu; Yajun Wang; Riling Chen; Guoda Ma (Molecular Genetics and Metabolism Reports, 2024)
Congenital disorder of glycosylation type Ia (CDG-Ia) is an autosomal recessive genetic disease caused by a mutation in the phosphomannomutase 2 (PMM2) gene. We have identified a 13-month-old boy who has been diagnosed with CDG-Ia. He displays several characteristic symptoms, including cerebellar hypoplasia, severe developmental retardation, hypothyroidism, impaired liver function, and abnormal serum ferritin levels. Through whole-exome sequencing, we discovered novel complex heterozygous mutations in the PMM2 gene, specifically the c.663C > G (p.F221L) mutation and loss of exon 2. Further analysis revealed that the enzymatic activity of the mutant PMM2 protein was significantly reduced by 44.97% (p < 0.05) compared to the wild-type protein.